"An Outpost of Progress": the Inequality of the Empire and the Reversal of Power - López Get, Anthony (2008)
This article analyzes both the power relations between the colonized subjects and the colonizers and the ideal of nation imposed by the europeans over its African subjects in Joseph Conrad's "An Outpost of Progress." We study how the invaders succumb to the impossibility of adapting to the prototype colonizer, and how a colonized character takes advantage of this situation in order to reverse, in a subtle way, his subordinated position.